Chemical Composition of Fresh Leaves Headspace Aroma and Essential Oils of Four Coriander Cultivars - Kumar, Sunjeet; Ahmad, Raza; Saeed, Sidra; Azeem, Muhammad; Mozūraitis, Raimondas; Borg-Karlson, Anna-Karin; Zhu, Guopeng (Frontiers in Plant Science, 2022)
Aroma is one of the key food characteristics determining consumers’ perception and acceptability of products. Coriandrum sativum L. is an aromatic herb commonly used as a food additive and taste enhancer. Besides the culinary applications, coriander is also used in traditional medicine, cosmetics, and the food industry. In this study, we aimed to determine aroma composition of fresh chopped leaves and essential oils extracted from the leaves of four coriander cultivars. The essential oils were extracted from the fresh leaves using steam distillation and volatile aroma components were collected from the headspace by solid phase micro extraction technique. Analyses were carried out by gas chromatography-mass spectrometry. Free radical scavenging activity of essential oils was determined by using 2,2-diphenyl-1-picrylhydrazyl assay. The essential oils were also investigated for their anti-microbial potential. The aroma of freshly chopped coriander leaves was characterized by thirteen compounds, including six aldehydes, four alcohols, one ester and one hydrocarbon. The essential oils were comprised of twenty-seven compounds, where (E)-2-decenal, decanal, (E)-2-dodecenal and (E)-2-tetradecenal were the main components in all cultivars. Free radical scavenging activity of the essential oil samples was in the range of 6-15%. The essential oils of Desi and Hybrid cultivars exhibited least minimum inhibitory concentration (MIC) against all tested bacterial strains. Fresh green leaves of the Desi and Peshawari cultivars were found to be the richest in six carbon chain length alcohols and acetates, which are important constituents of the aroma giving a characteristic odor referred to as the ‘green note’. The Hybrid cultivar showed the highest free radical scavenging activity, bearing the highest amount of antioxidants. The study revealed that the fresh leaves HS aroma of Desi and Hybrid cultivars were different, however, their essential oils possessed almost similar chemistry and anti-bacterial activity.